Efficient Closed Form Cut-Off Planes and Propagation Planes Characteristics for Dielectric Slab Loaded Boundary Value Problems - Junaid Zafar (Institute of Advanced Engineering and Science, 2012)
The geometrical relationship between the cut-off and propagating planes of any waveguide system is a prerequisite for any design process. The characterization of cut-off planes and optimisation are challenging for numerical methods, closed-form solutions are always preferred. In this paper Maxwells coupled field equations are used to characterise twin E-plane and H-plane slab loaded boundary value problems. The single mode bandwidths and dispersion characteristics of these structures are presented and critically compared. The impact of slab mobility upon cut-off and propagations planes has been envisaged. The presented formulation has been extended further to derive a vectorized Green function expression linking electric and magnetic fields for the characterization of planar waveguide structures.